(untitled) (Journal Of Educational and Psychological Researches, 2022)
The study aimed to identify the psychological counseling skills and the strength of the ego in the educational counselors, and to identify the relationship of statistical significance between the psychological counseling skills and the strength of the ego in the educational counselors, and to identify the differences of statistical significance in the relationship between psychological counseling skills and the strength of the ego in the guides according to the gender variable(male, Females), the number of sample (100) guides, including (50) males and (50) females from the area of ​​Atifiya and Qadissiya and Ameriya in the Directorate of Education Karkh / 1, the researcher adopted a scale of psychological counseling skills prepared by Shaheen (2014), which consists Of (50) paragraphs, and the researcher built m The study concluded that the educational counselors have psychological counseling skills and high level of ego strength, and there is a statistically significant relation between the psychological counseling skills and the strength of the ego in the educational counselors, There are no statistically significant differences in the relation between Skills of psychological guidance and strength of the ego in the educational counselors according to gender variable,